UMPSA hosts RBTX Petrosains Challenge Eastern Zone 2024 - Naqiah, Puaad (UMPSA, 2024)
PEKAN, 4 September 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) hosted the RBTX Petrosains Challenge East Zone 2024 Competition at the Multipurpose Hall, UMPSA Pekan.